Contexts and Influences on the Need for Personal Flexibility for the 21st Century, Part II - Herr, Edwin L. (Canadian Journal of Counselling and Psychotherapy, 1993)
Personal flexibility appears to be of growing importance in a global economy. However, personal flexibility does not occur spontaneously. It must be nurtured by schools and facilitated by counsellors in education, work and community settings. The need for new paradigms of career counselling, psychoeducational models, and testing are discussed as are possibilities for cross-national information systems and support for those engaged in cross-national migration.